Empowerment and leadership effectiveness amongst Malaysian managers - Shariff, Suriati (2005)
The study is focused on empowerment and leadership effectiveness amongst Malaysian managers .The objective of the research is to identify the level of empowerment practiced by Malaysian Managers, to determine whether demographic factors (leader’s characteristics and organization’s characteristics) contribute to the relationship between empowerment and leadership effectiveness and finally to ascertain the relationship between empowerment components (impact, competence, self-determination and meaning) with leadership effectiveness.